Application of environmental bacteria as potential methods of azo dye degradation systems - G. Manjarrez Paba; R. Baldiris Ávila; D. Baena Baldiris (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES:The objective of this study isto present a description of the main characteristics of azo dyes and the different treatment methods used to remove them from water. There is a special emphasis given to the benefits associated with biological treatment, predominantly those related to the use of bacteria, which has to do with its competitive advantages over other microorganisms in the dye degradation processes. METHODS: The topic to be addressed was first defined through workshops with the research group. The literature review was carried out following several inclusion/exclusion criteria: the year of publication, as the selection was limited to studies published between 2010 and 2020, the focus of the investigation, which had to be related to the efficiency of different techniques for the remediation of ecosystems contaminated with azo dyes and, lastly, that the studies also discussed the use of environmental bacteria in dye degradation processes. FINDING: The efficiency of bacteria to degrade azo dyes ranges from 63-100%, the most efficient being: Marinobacter sp, Sphingobacterium sp, Enterococcus faecalis, Enterococcus casseliflavus. The bacteria that, reportedly, have greater efficiency for simultaneously removing the dye-metal complex are Bacillus circulans and Acinetobacter junii. CONCLUSION: Traditional strategies for the treatment of effluents contaminated with azo dyes are limited to physical and chemical processes that have a high energy and economic cost. For these reasons, current challenges are focused on the use of environmental bacteria capable of transforming dyes into less toxic compounds.